The role of interfaith dialogue in enhancing social tolerance in multicultural communities - Seran, Yanuarius (Jurnal Konseling dan Pendidikan, 2025)
In increasingly diverse societies, interfaith dialogue plays a crucial role in fostering social tolerance and mutual understanding among different religious and cultural groups. This study employs a qualitative research approach using literature review and library research methods to explore how interfaith dialogue contributes to social cohesion in multicultural communities. By analyzing various scholarly works, reports, and case studies, this research identifies the key factors that enhance or hinder effective interfaith engagement. The findings suggest that interfaith dialogue serves as a bridge to reduce prejudices, correct misconceptions, and build trust between religious communities. Moreover, it fosters a culture of peace by promoting shared values, empathy, and respect for diversity. The study also highlights challenges such as power imbalances, religious fundamentalism, and political manipulation that can obstruct meaningful dialogue. Successful interfaith initiatives often incorporate inclusive participation, open communication, and institutional support to ensure long-term impact. The implications of this study emphasize the need for governments, religious leaders, and civil society to actively support and institutionalize interfaith dialogue as a strategy for preventing religious conflicts and promoting harmonious coexistence. Future research is encouraged to examine the role of digital platforms and social media in expanding interfaith dialogue efforts. Understanding the dynamics of interfaith interactions provides valuable insights for policymakers and community leaders striving to cultivate tolerant, cohesive, and inclusive societies in the face of growing multicultural challenges.